Aerothermal Postflight Analysis of the Sharp Edge Flight Experiment-II - Gülhan, A.; Neeb, Dominik; Thiele, Thomas; Siebe, Frank (Journal of Spacecraft and Rockets, 2015)
The aerothermal instrumentation of the Sharp Edge Hypersonic Flight Experiment SHEFEX-II, which was launched from Andøya Rocket Range on top of a two-stage rocket configuration, provided very useful flight data. Complementary to the pressure data, heat flux rate and surface temperature were measured at selected locations on the payload along the complete ascent and descent trajectory. Measured heat flux rate and pressure fluctuations show excellent correlation with angle-of-attack variations. Calculated heat flux evolution using a hypersonic boundary-layer code along the trajectory is in reasonable agreement with measured heat flux data during flight. Boundary-layer transition was measured at a boundary-layer edge Reynolds number of approximately 3⋅10E6 for both ascent and descent phases. The complementary analytical and numerical study for the flight rebuilding at selected flight points provided very useful data and allowed better understanding of the physical phenomena. Finally, a combined analytical–numerical approach was validated and applied for the computation of the heat flux rate along the flight trajectory. This verified method can be used for the design and analysis of future hypersonic flights of slender vehicles.